Flood Hazard Mapping and Risk Evaluation in the Lower Karnali River Basin of Nepal - Chhinal, Laxmi; Thakuri, Sudeep; Mathema, Ajay bhakta; Dulal, Bipin; Khanal, Sanjay Nath (Geographical Journal of Nepal, 2026)
This study presents flood hazard mapping and risk assessment using a hydrodynamic simulation in HEC-RAS tool, focusing on a 38 km stretch of the river from Chisapani to the Nepal-India border in the Lower Karnali River Basin (KRB). A time series of daily mean discharge records from the Chisapani gauging station was used for model simulations. Flood magnitudes of 10-, 20-, 50-, and 100- year return periods (YRPs) were estimated using Gumbel’s distribution, with the 100-YRP daily discharge of 20,343 m3/s. Field surveys were conducted in flood-prone areas of Rajapur Municipality using the Vulnerability and Risk Assessment (VRA) framework. Results show that parts of Rajapur Municipality, Wards #1, #3, #4, and #7 are susceptible to inundation, even during normal flood events, with water depths reaching upto 10 m posing significant risk to the communities inhabiting in these areas. Agricultural land is particularly exposed, posing serious risks to food security and livelihoods. Moreover, even after a five-year return period, the 2014 flood simulations (equal to a 100-YRP) indicate that these wards remains highly vulnerable. This findings emphasizes the urgent need for improved settlement planning and the development of effective flood control measures in Rajpur Municipality.